Acute sleep loss alters circulating fibroblast growth factor 21 levels in humans: A randomised crossover trial. (2nd September 2021) - Mateus Brandão, Luiz Eduardo; Espes, Daniel; Westholm, Jakub Orzechowski; Martikainen, Teemu; Westerlund, Nestori; Lampola, Lauri; Popa, Alexandru; Vogel, Heike; Schürmann, Annette; Dickson, Suzanne L.; Benedict, Christian; Cedernaes, Jonathan
Summary: The hormone fibroblast growth factor 21 (FGF21) modulates tissue metabolism and circulates at higher levels in metabolic conditions associated with chronic sleep–wake disruption, such as type 2 diabetes and obesity. In the present study, we investigated whether acute sleep loss impacts circulating levels of FGF21 and tissue‐specific production, and response pathways linked to FGF21. A total of 15 healthy normal‐weight young men participated in a randomised crossover study with two conditions, sleep loss versus an 8.5‐hr sleep window. The evening before each intervention, fasting blood was collected. Fasting, post‐intervention morning skeletal muscle and adipose tissue samples underwent quantitative polymerase chain reaction and DNA methylation analyses, and serum FGF21 levels were measured before and after an oral glucose tolerance test. Serum levels of FGF21 were higher after sleep loss compared with sleep, both under fasting conditions and following glucose intake ( 27%–30%, p = 0.023). Fasting circulating levels of fibroblast activation protein, a protein which can degrade circulating FGF21, were not altered by sleep loss, whereas DNA methylation in the FGF21 promoter region increased only in adipose tissue. However, even though specifically the muscle exhibited transcriptional changes indicating adverse alterations to redox and metabolic homeostasis, no tissue‐based changes were observed in expression of FGF21, its receptors, or selected signalling targets, in response to sleep loss. In summary, we found that acute sleep loss resulted in increased circulating levels of FGF21 in healthy young men, which may occur independent of a tissue‐based stress response in metabolic peripheral tissues. Further studies may decipher whether changes in FGF21 signalling after sleep loss modulate metabolic outcomes associated with sleep or circadian disruption.